Evaluation and Decomposition of Tourism Inefficiency Considering Heterogeneous Technology: An Empirical Study from China - Zha, Jianping; He, Dongqin; Zhu, Ying; Yang, Xiaojie; Luo, Mingzhi (Journal of hospitality & tourism research (Washington, D.C.), 2022)
Considering both sectoral and regional heterogeneities, this article develops a structural meta-frontier slacks-based measure data envelopment analysis model to decompose the inefficiency level, input reduction and output expansion potentials and efficiency change into three components: sectoral heterogeneity, regional heterogeneity, and resource utilization. Subsequently, an empirical study of China’s provincial tourism subsectors between 2000 and 2014 is conducted. The results show that regional heterogeneity and resource utilization failure are the main contributors to the inefficiency of travel agencies, but the inefficiency of star-rated hotels and tourist attractions are dominated by sectoral heterogeneity. The tourism inefficiency of China is mainly characterized by insufficient output rather than input redundancy, and there are significant differences in the sources of output expansion potential for different tourism subsectors. In addition, the driving force for improving the efficiency of travel agencies ascribed to resource utilization capabilities are pure technological progress and technology scale change.